Aspek Sosial Masyarakat Pinggiran dalam Kumpulan Puisi Aku Ingin Jadi Peluru pada Bagian Buku Kedua Ketika Rakyat Pergi Karya Wiji Thukul Kajian Sosiologi Sastra Sebagai Bahan Ajar Di SMA N 1 Tawangsari - Sa'id, Burhanuddin Ahmad, Drs. Adyana Sunanda, M.Pd (2017)
Abstract This study aimed to describe (1) the background of the socio-historical Wiji Thukul (2) the inner structures that build up in the second book Ketika Rakyat Pergi, (3) social aspects contained in the second book Ketika Rakyat Pergi study sociology of literature, and (4) implementation of the social aspects of research are contained in the Ketika Rakyat Pergi by Wiji Thukul as a literary teaching materials in SMA N 1 Tawangsari. This study used descriptive qualitative method. The object of this study is the social aspect of rural communities in the collection of poems Aku Ingin Jadi Peluru that is focused on the second part of the book Ketika Rakyat Pergi by Wiji Thukul. The data in this study is the word, quotes and sentences on a collection of poems Aku Ingin Jadi Peluru that is focused on the second part of the book Ketika Rakyat Pergi Wiji Thukul. Sources of primary data in this study of a collection of poems Aku Ingin Jadi Peluru published by Indonesia Tera in 2000 focused on the second part of the book Ketika Rakyat Pergi by Wiji Thukul. Secondary data sources in this study in the form of books, journals, articles that have relevance to this study. This study uses a sampling technique. Data collection techniques used in this study is a document analysis techniques. Mechanical validity of the data used in this study is a technique trianggulasi data. Data analysis technique used is an interactive model. Based on the analysis performed, it can be summed up as follows: (1) the socio-historical background Wiji Thukul that he was born on August 26, 1963 Solo. Wiji Thukul own poems gave voice against the injustices in society, (2) based on the structure a mind that building a collection of poems Aku Ingin Jadi Peluru that is focused on the second book Ketika Rakyat Pergi by Wiji Thukul found theme (sense), feelings of the poet (felling), tone or attitude of the poet to the reader (tone), and the mandate (intention), ( 3) social aspects of rural communities are found in the form of (a) the social aspect rim of poverty, (b) social aspect periphery of social protest as a result of injustice, and (c) social aspects of rural communities about the social reality, (4) the results of this study can be implemented in learning Indonesian language and literature in high school the first semester class X because according to three criteria, namely language teaching materials, psychology and cultural background. Keywords: social aspects, teaching materials in high school, when the People Go, and in rural communities.